Determination of Glutathione and Cysteine in Human Breast Milk by High-Performance Liquid Chromatography with Chemiluminescence Detection for Evaluating the Oxidative Stress and Exposure to Heavy Metals of Lactating Women. (1st November 2020) - Wei, Lanlan; Lu, Xiaoting; Kang, Xuejun; Song, Yuan
Abstract: Exposure to heavy metals may affect a vast array of biochemical and nutritional processes in the human body. The toxic manifestations of these metals are caused primarily due to the imbalance between pro-oxidant and antioxidant homeostasis which is termed as oxidative stress. A high-performance liquid chromatography–chemiluminescence (HPLC-CL) method was developed for the simultaneous determination of two antioxidants, glutathione and cysteine, in human breast milk. The HPLC system included a C18 analytical column with a mobile phase composed of 1.0% methanol. The aminothiols were eluted from the C18 column, mixed with formaldehyde and potassium permanganate solutions, and subsequently monitored by a chemiluminescence detector. The new method was validated by monitoring glutathione and cysteine in human breast milk of volunteers from the Gusu and Industrial Districts of Suzhou, China. Four heavy metals in atmospheric particulate matter collected from the two districts were also determined by inductively coupled plasma–mass spectrometry (ICP-MS). The results demonstrated that the concentrations of cysteine and glutathione were significantly ( p < 0.05) lower in human breast milk from the subjects living in the Gusu region of Suzhou, Jiangsu Province, China compared to an industrial district. These results were inversely correlated with the concentration levels of the toxic metals in collected atmospheric particulate matter. The decrease in the glutathione and cysteine concentrations in human breast milk appeared to be due to oxidative stress in the breast-feeding mothers.